Comparison of endogenously expressed fluorescent protein fusions behaviour for protein quality control and cellular ageing research - Kara L. Schneider (Nature Portfolio, 2021)
Abstract The yeast Hsp104 protein disaggregase is often used as a reporter for misfolded or damaged protein aggregates and protein quality control and ageing research. Observing Hsp104 fusions with fluorescent proteins is a popular approach to follow post stress protein aggregation, inclusion formation and disaggregation. While concerns that bigger protein tags, such as genetically encoded fluorescent tags, may affect protein behaviour and function have been around for quite some time, experimental evidence of how exactly the physiology of the protein of interest is altered within fluorescent protein fusions remains limited. To address this issue, we performed a comparative assessment of endogenously expressed Hsp104 fluorescent fusions function and behaviour. We provide experimental evidence that molecular behaviour may not only be altered by introducing a fluorescent protein tag but also varies depending on such a tag within the fusion. Although our findings are especially applicable to protein quality control and ageing research in yeast, similar effects may play a role in other eukaryotic systems.